An improved and simplified protocol to combine Golgi-Cox staining with immunofluorescence and transmission electron microscopy techniques. (January 2021) - Pedrazzoli, Matteo; Medelin, Manuela; Marchiotto, Federica; Cisterna, Barbara; Malatesta, Manuela; Buffelli, Mario
Abstract: Approaches utilizing multiple analysis techniques on a single sample are highly desirable in research, especially to reduce the number of animals and obtain the maximum information. Golgi-Cox staining is a widely used method for characterizing axon and dendritic morphology and several attempts to combine this technique with immunofluorescence and transmission electron microscopy have been proposed. With few exceptions, most of the protocols were characterized by a high degree of complexity and low reproducibility. Here we show a simplified procedure of perfusion, fixation and staining of brain tissues that allows Golgi-Cox staining, immunofluorescence and transmission electron microscopy in the same sample, to obtain high-quality images with a low-cost procedure. The main novelty in this protocol is the possibility of performing Golgi-Cox staining after the perfusion and post-fixation of brain tissue with a buffered solution containing, not only formaldehyde, but also glutaraldehyde. This renders the tissue suitable for electron microscopy, but it is also compatible with immunofluorescence staining. This combined protocol can be used in most neuroscience laboratories as it does not require special equipment and skills. This protocol will be useful in a broad range of neuroscience topics to study morphological changes during brain development and plasticity in physiological and pathological conditions. Highlights: A simplified procedure to obtain Golgi-Cox staining, IF and TEM in the same sample. The protocol is simple, cheap and does not require special equipment and skills. Perfusion–fixation with paraformaldehyde and glutaraldehyde yields good results. It will be useful to evaluate morphological changes in many neuroscience topics.